2017
DOI: 10.3389/fpsyg.2017.00379
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy Is Chaotic—(Not Only) in a Computational World

Abstract: Objective: The aim of this article is to outline the role of chaotic dynamics in psychotherapy. Besides some empirical findings of chaos at different time scales, the focus is on theoretical modeling of change processes explaining and simulating chaotic dynamics. It will be illustrated how some common factors of psychotherapeutic change and psychological hypotheses on motivation, emotion regulation, and information processing of the client's functioning can be integrated into a comprehensive nonlinear model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 106 publications
1
75
0
Order By: Relevance
“…Although not the only avenue of interest, having found these continuous and discontinuous changes means we should not overlook a complex dynamical systems explanation for understanding patterns of treatment response in depression (Abel et al, 2016;Hayes & Strauss, 1998). Some empirical research has supported the idea that sudden changes in symptoms may be indications of a critical shift in the mood system, where a move toward a more adaptive state is reached after the positive influence of therapy (Schiepek, 2009;Schiepek et al, 2018Schiepek et al, , 2017van de Leemput et al, 2014;Wichers et al, 2016). Examining whether sudden gains in depression indicate tipping points is relevant, as dynamical systems theory may provide us with methods to anticipate changes in symptoms or depressive burden.…”
Section: Discussionmentioning
confidence: 99%
“…Although not the only avenue of interest, having found these continuous and discontinuous changes means we should not overlook a complex dynamical systems explanation for understanding patterns of treatment response in depression (Abel et al, 2016;Hayes & Strauss, 1998). Some empirical research has supported the idea that sudden changes in symptoms may be indications of a critical shift in the mood system, where a move toward a more adaptive state is reached after the positive influence of therapy (Schiepek, 2009;Schiepek et al, 2018Schiepek et al, , 2017van de Leemput et al, 2014;Wichers et al, 2016). Examining whether sudden gains in depression indicate tipping points is relevant, as dynamical systems theory may provide us with methods to anticipate changes in symptoms or depressive burden.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral reaction has perceived benefits and costs, reinforcing or inhibiting the behavior Note that in this paper, we primarily focus on modeling linear differential equations. Extending the framework to including non-linear equations would be a relevant step for future research, given that prior literature found that psychotherapeutic processes are often chaotic, a feature that is characteristic for non-linear dynamics [41,51]. For the sake of implementation, however, we decided to focus on linear equations, since many aspects of non-linear dynamics require an extensive mathematical understanding.…”
Section: Methodsmentioning
confidence: 99%
“…Sim, Gwee, and Bateman [40] identified five key advantages associated with formulating thorough case conceptualizations in clinical practice: (a) the integration/relation of multiple problems of a patient, (b) the explanatory nature of the resulting model, (c) the prescription of interventions, (d) the prediction of outcomes, and (e) the support for the therapeutic relationship. Schiepek and colleagues [36,37,41] pioneered the integration of case formulation and idiographic system modeling and argued that these key advantages could be strengthened through computational models. Clinicians are required to make more rigorous decisions in specifying relations in the case conceptualization, which makes the formalization of idiographic theories a promising avenue to foster more scientific practices in designing patient-tailored treatment.…”
Section: The Role Of Computational Models In Bridging the Scientist-pmentioning
confidence: 99%
See 1 more Smart Citation
“…While I think it is at least plausible to consider intrapersonal ratings as (more or less) reliable, I believe that interpersonal ratings are highly questionable due to the qualia problem. Based on quantification, promising models of psychological processes have been developed by Schiepek et al [14], Tschacher et al [13] and others.…”
Section: Criteria For Ops and Syndromsmentioning
confidence: 99%